Selection of DNA aptamers using atomic force microscopy - Miyachi, Yusuke (Oxford University Press, 2010)
Atomic force microscopy (AFM) can detect the adhesion or affinity force between a sample surface and cantilever, dynamically. This feature is useful as a method for the selection of aptamers that bind to their targets with very high affinity. Therefore, we propose the Systematic Evolution of Ligands by an EXponential enrichment (SELEX) method using AFM to obtain aptamers that have a strong affinity for target molecules. In this study, thrombin was chosen as the target molecule, and an ‘AFM-SELEX’ cycle was performed. As a result, selected cycles were completed with only three rounds, and many of the obtained aptamers had a higher affinity to thrombin than the conventional thrombin aptamer. Moreover, one type of obtained aptamer had a high affinity to thrombin as well as the anti-thrombin antibody. AFM-SELEX is, therefore, considered to be an available method for the selection of DNA aptamers that have a high affinity for their target molecules.